APLIKASI KONSENTRASI EKSTRAK DAUN Annona muricata L. TERHADAP Spodoptera litura F. PADA TANAMAN KEDELAI - Fitri Sundari; Yusmar Mahmud; Tahrir Aulawi (UIR Press, 2021)
Spodoptera caterpillars belong to the category of pests that cause serious damage to crops, therefore, to improve crops, environmentally friendly herbicides such as sorrel are needed. The aim of this research was to obtain a sorrel leaf extract that is effective in controlling Spodoptera. The study was carried out in the Laboratory of Pathology, Microbiological Entomology, Soil and Experimental Farm of the Faculty of Agriculture and Animal Sanctity, Sultan Syarif Kasim Riau National Islamic University, and the Chemistry Laboratory of the Faculty of Mathematics of Natural Sciences of Riau University from February to March 2019. This study used a non-factorial complete randomized design consisting of 6 treatments and 3 replications, thus there were 18 treatment units. The parameters observed were daily mortality, percentage of larvae stop feeding, larvae transform into rabbits, lethal concentration 50%. Research results showed that the effective concentration was 20% and the increase in concentration did not affect larval mortality.